MACROSCOPIC EXAMINATION OF BREAST DENSITY CORRELATION WITH MAMMOGRAPHIC BREAST DENSITY IN BREAST CANCER–CONSERVING SURGERY: A RETROSPECTIVE ANALYSIS - Reis, Yedda Nunes; Mota, Bruna Salani; Ricci, Marcos Desiderio; Shimizu, Carlos; Aguiar, Fernando Nalesso; Cardoso, Natalia Paula; Baracat, Edmund Chada; Filassi, José Roberto (Mastology, 2021)
Objective: The aim of this study is to evaluate the association between mammographic breast density (MBD) and macro-scopic examination of breast density (MEBD), as well as the association between MEBD and multiple clinical and tumoral characteristics. Methodology: The secondary (i.e., retrospective) analysis from a prospective database (BREAST-MRI trial) was performed. Patients with breast cancer stages 0 to III for breast-conserving surgery, from November 2014 to October 2018, were selected. All patients were evaluated with clinical examination, breast ultrasound, and mammography and stratified by MBD. Then, they were randomized on a 1:1 basis in two groups whether to perform breast magnetic resonance imaging. Analysis of the subset of patients’ MEBD in the clinical trial was not prespecified. MEBD was estimated by cal-culating the ratio of stromal and fatty tissues in each breast histopathological sample, and then, patients were classified similarly to ACR BI-RADS® criteria. Results: A total of 431 MEBD were selected for the analysis. MEBD classification was distributed as follows: 303 (70.3%) were classified as A, 85 (19.7%) as B, 36 (8.4%) as C, and 7 (1.6%) as D. There is no associa-tion between MBD and MEBD in our breast surgical specimens, such that MEBD A, B, C, and D were associated with MBD in 22 (97.1%) of 24 A breasts, 34 (18.2%) of 187 B breasts, 26 (13.1%) of 199 C breasts, and 1 (4.8%) of 21 D breasts (p<0.001). Breasts with the highest fat content in the macroscopic analysis were associated with older patients, higher body mass index, multiparity, and postmenopausal status (p=0.001). There was no difference among groups regarding the history of hormone replacement therapy, clinical stage, and immunohistochemical. Conclusion: Our study shows that MEBD does not hold a close correlation with MBD, according to the ACR BI-RADS classification.